2012
DOI: 10.1002/asia.201100904
|View full text |Cite
|
Sign up to set email alerts
|

First‐Principles Investigation of the Electronic and Conducting Properties of Oligothienoacenes and their Derivatives

Abstract: Herein, we calculated reorganization energies, vertical ionization energies, electron affinities, and HOMO–LUMO gaps of fused thiophenes and their derivatives, and analyzed the influence of different substituents on their electronic properties. Furthermore, we simulated the angular resolution anisotropic mobility for both electron‐ and hole‐transport, based on quantum‐chemical calculations combined with the Marcus–Hush electron‐transfer theory. We showed that: 1) styrene‐group substitution can effectively elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…Previous experimental and theoretical studies showed that the HOMO level increases, while the LUMO level and the HOMO−LUMO gap decrease as the conjugated chain length is elongated. 23,26,27 The above differences in VIP values, EA values, and HOMO−LUMO gaps are also associated with the smaller effective conjugation length of compound 9 than compound 14. In compound 9, the steric effect between the H atoms in bilateral and core phenyl groups induces large dihedral angles between the bilateral benzene rings and the molecular core plane (α = 40.2°), which decrease effective conjugation length along long molecular axis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous experimental and theoretical studies showed that the HOMO level increases, while the LUMO level and the HOMO−LUMO gap decrease as the conjugated chain length is elongated. 23,26,27 The above differences in VIP values, EA values, and HOMO−LUMO gaps are also associated with the smaller effective conjugation length of compound 9 than compound 14. In compound 9, the steric effect between the H atoms in bilateral and core phenyl groups induces large dihedral angles between the bilateral benzene rings and the molecular core plane (α = 40.2°), which decrease effective conjugation length along long molecular axis.…”
Section: Resultsmentioning
confidence: 99%
“…20 The fused structure of DTT can promote π-stacking which is predicted to be a favourable motif for high charge transport in devices. [21][22][23] This approach can help to create materials with low-energy electronic transitions based on donor-acceptor interactions. [24][25][26] In this context, Kim and Navarette designed and synthesized a series of D-π-D and D-π-A type molecules base on the DTT unit for nonlinear optical materials.…”
Section: Introductionmentioning
confidence: 99%
“…To explain how chemical composition, geometric structure, and packing affect the transport properties, Han and coworkers developed a theoretical method to investigate the relationship between angular resolution anisotropic mobilities and molecular packing architecture parameters (r, h, and c) as well as underlying electronic properties (reorganization energy k and intermolecular electronic coupling V) by first-principle quantum mechanics (QM) calculations based on Marcus-Hush theory [47,48]. They have investigated systematically the anisotropic mobilities in a series of organic semiconductors such as acene, acene derivatives and rubrene, which coincide with experimental observations very well [49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 58%